JAVA COASTAL CURRENT AT NORTHWEST AND SOUTHEAST MONSOON IN SOUTHWEST SUMATRA - La Ode Nurman Mbay; I Wayan Nurjaya (Pusbindiklat - LIPI, 2011)
The Java Coastal Current (JCC) is valuable information since its supplies water mass to South Indonesian water. The data analysis was done using temperature, salinity and depth informations from CTD (Conductivity, Temperature, and Depth). Those informations was calculated based on Neuman and Pierson (1966) with 600 db in reference level, in order to obtain the dynamic topography and geostrophy velocity. The results showed that there was a dynamic depth divergence between shore and the off shore, both was occured in Northwest monsoon and Southeast monsoon. Hence it was acting as a trigger of the geostrophy current toward Southeast with maximum velocity was 18.81 cms -1 and 1.53 sv of transport volume.